Performance Analysis of Compression Ignition Engines Using Emulsion Fuel Blended with Aluminium Oxide Nanoparticles - A. R. Sivaram; N. Prabhu; R. Praveen Kumar; G. Navaneethakrishnan; R. Palanisamy; Kareem M. AboRas; Mohit Bajaj; Repele Djidimbele; Kidmo Kaoga Dieudonné; V. Leela Vinodhan (Advances in Materials Science and Engineering)
One of the excellent choices for compression ignition engines is emulsions. The current experimental analysis deals with transesterified Pongamia biodiesel. This work gives a substantial track to synthesize and to enhance fuel by including aluminium oxide nanoparticles. Emulsification is used to prepare fuel consisting of 88% of Pongamia biodiesel, 10% water, and 2% surfactants with series chemical emulsification techniques. This is then mixed with the ratio of 50 ppm and 100 ppm by mass with aluminium oxide nanoparticles by employing ultrasonication techniques. This work is carried out on compression ignition engines in different phases using biodiesel, nanoparticles, surfactants, and water. It was inferred from the results that there was a considerable enhancement in performance and decrease in emission when compared with diesel. It is found that the system exhibited 15% improvement in brake thermal efficiency and 45% reduction in oxides of nitrogen. The system exhibited considerable improvement in performance and reduction in emission.